Description of the female and new characteristics of the male of Phlugis gracila Nickle, 2003 (Orthoptera: Tettigoniidae: Meconematinae) with new behavioral data - Mendes, Diego Matheus De Mello; Oliveira, Jomara Cavalcante De; Sobral, Rafael; Marques, Guilherme Alves (Zootaxa, 2017)
The description of the female of Phlugis gracila and the addition of new characters to the original male description are provided. The description of the male stridulatory file and genitalic morphology is noted for the first time. This is the first record for the species in Brazil (Amazonas) and its natural history is noted.